(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Some students, who attach no importance to reading aloud, believe that the reading and writing should follow the listening and speaking. However, “reading aloud” plays an important role in the English learning process. Why must we read aloud? First of all, English is a kind of phonic language, which uses the alphabetic writing. Moreover, English is a subject with practice. At the same time, “reading aloud” also is an important part in education for all- around development, which has several functions in English teaching. But in recent years, some English teachers paid more attention to the accumulation of reading skill than to reading itself, and neglected to foster the reading practice ability. Some teachers even believe that it is enough to make the students to open their mouths. In fact, reading aloud in English Teaching is very demanding.